Analisis Miskonsepsi Peserta Didik pada Materi Asam Basa Menggunakan Instrumen Three-Tier Diagnostic Test - Ekawisudawati, Ekawisudawati; Wijaya, Mohammad; Danial, Muhammad (Chemistry Education Review (CER), 2021)
The study aims to analyze students' misconceptions using a three-tier diagnostic test on acid-base material. The type of research used in this study is descriptive research. This research was conducted at SMAN 1 Mamuju to grade XI MIPA students. Data collection techniques employed diagnostic test in the form of multiple-choice stratified. The first level contained the students' answers, the second level was the reason for the answers, and the last level was the level of confidence. Data analysis was conducted by looking for the percentage of misconceptions from each concept in Acid-Base materials, namely the concept of acid-base theory, pH indicators of acid-base solutions, strength of acids and bases, and calculation of pH of acid and base solutions. The results show that the category of students' misconceptions on acid-base materials using the three-tier diagnostic test instrument is the M1 category. In this category, students answered incorrectly at the first and second levels but were sure that the answers at both levels were correct. The percentage obtained in the M1 category is 33.87% with moderate category. Students' misconceptions occur in the concept of acid-base theory according to Bronsted Lowry with a percentage of 70.33% in item 4 and 73.08% in item 18. The concept of pH indicator of acid-base solutions with a percentage of 73.08% in item number 9 while for the concept of the strength of acids and bases with a percentage of 76.36% in item 9. For the concept of calculating the pH of an acid-base solutions, 3 items are obtained that fall into the category of high misconceptions, namely item 14 with a percentage of 83.52%; item 16 with a percentage of 82.42%; and 20 items with a percentage of 78.02%. The causes of misconceptions in students are due to the incomplete reasoning, students' abilities, students' interest in learning, and teacher’s teaching methods.